COHESIVE DEVICES FOUND IN THE MAXX BRIDES MAGAZINE - Ni Wayan Suastini; Ni Kadek Ayu Suartini (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2018)
ABSTRACT This study attempts to describe the cohesive devices used in the Maxx Brides Magazine. The data of this study were taken from the articles found in the Maxx Brides Magazine on March Edition 2017. The data was collected by observation method. The analysis of the data was conducted by descriptive qualitative method. There are at least two factors that influence the text, those are cohesion and coherence. Cohesion provides the relation of meaning that exists within the text. Meanwhile, coherence is semantic property of discourse which is formed by interpretation of each relative sentence to other sentences .the coherent text is meaningful, unified and gives the impression. The qualitative analysis was applied in analyzing the sample texts. The finding showed that the demonstrative reference was the type most frequently used grammatical cohesion and synonym were the most frequently used lexical cohesion in the articles. Keyword: cohesive devices, maxx brides magazine